The An-Nahdliyah and The Yanbu'a Method in Learning to Read the Qur'an in the Vocational High School: Comparative Study - Suminto Suminto; Arinatussadiyah Arinatussadiyah (ISTAWA, 2020)
This research is motivated because there are still very few people who can read the Al-Qur'an with the correct recitation. Efforts must be made to conduct Al-Qur'an learning in educational institutions, both formal and informal. This paper aims to describe the implementation and implications of learning to read the Koran with an-nahdliyah and yanbu'a methods. This research uses a qualitative approach. Data analysis techniques used single case analysis and cross-case analysis. Research results: (1) The implementation of Al-Qur'an reading and writing learning with an-nahdliyah method in Nahdlatul 'Ulama Vocational High School (SMK-NU) and yanbu'a method in Islamic Vocational High School (SMKI) Al-Azhaar Tulungagung which aims so that students can read the Qur'an in accordance with the science of recitation with implementation: opening prayer, classical, private, evaluation, motivation, and closing prayer. (2) Learning material at SMK-NU: volume books (volumes 1-6), Al-Qur'an, and the book "Provisions for Prospective Leaders. While the material in the ISMS: beginner Juz, Juz 1-7, Al-Qur'an, and rote learning. (3) Implications of learning with an-nahdliyah method and yanbu’a methods include. In essence, students can read the Qur'an by the knowledge of recitation and can write the letters of the Qur'an correctly and adequately.Penelitian ini dilatarbelakangi karena masih sedikitnya masyarakat yang dapat membaca Al-Qur’an dengan tajwid yang benar. Upaya yang harus dilakukan mengadakan pembelajaran Al-Qur’an di lembaga-lembaga pendidikan, baik formal maupun non formal. Naskah ini bertujuan mendeskripsikan implementasi dan implikasi pembelajaran baca tulis alqur'an dengan metode an-nahdliyah dan yanbu'a. Penelitian ini menggunakan pendekatan kualitatif. Teknik analisis data menggunakan analisis kasus tunggal dan analisis lintas kasus. Hasil penelitian: (1) Pelaksanaan pembelajaran baca tulis Al-Qur’an dengan metode an-nahdliyah di Sekolah Menengah Kejuruan Nahdlatul 'Ulama (SMK-NU) dan metode yanbu’a di Sekolah Menengah Kejuruan Islam (SMKI) Al-Azhaar Tulungagung yang bertujuan agar peserta didik dapat membaca Al-Qur’an sesuai dengan ilmu tajwid dengan implementasi: do’a pembuka, klasikal, privat, evaluasi, motivasi, dan do’a penutup. (2) Materi pembelajarannya di SMK-NU: buku jilid (jilid 1-6), Al-Qur’an, dan buku “Bekal Calon Pemimpin. Sedangkan materi di SMKI: Juz pemula, Juz 1-7, Al-Qur’an, dan materi hafalan. (3) Implikasi dari pembelajaran dengan metode an-nahdliyah dan metode yanbu’a antara lain: peserta didik dapat membaca Al-Qur’an sesuai dengan ilmu tajwid dan dapat menulis huruf Al-Qur’an dengan baik dan benar.